Design and Simulation of a Sugarcane Juice Extractor. - Akampurira, Amon (Kabale University, 2025)
This project involved the design of a sugarcane juice extractor machine engineered to crush sugarcane at a rate of 14-15 kg per hour, catering to the increasing demand for fresh sugarcane juice in small to medium-scale commercial settings. The primary objective is to optimize juice yield while maintaining high operational efficiency. The design features a robust roller system capable of processing sugarcane stalks of various sizes, ensuring effective extraction with minimal wastage. The use of food-grade materials that as stainless steel in all components that come into contact with the juice is a key focus, ensuring the design adheres to strict hygiene standards. The machine is designed to be compact and user-friendly, making it suitable for vendors who may have limited space and technical expertise. Although this project is focused on the design phase, it provides a detailed and comprehensive blueprint that can be further developed into a fully operational machine. The design process involved careful consideration of factors such as juice yield, energy consumption, and ease of maintenance, ensuring that the final design meets market needs.